Redefining the Economics of Geriatric Orthopedics. (December 2014) - Truntzer, Jeremy; Nacca, Christopher; Paller, David; Daniels, Alan H
Introduction: The heath care system in the United States is in the midst of a transition, in large part to help accommodate an older and more medically complex population. Central to the current evolution is the reassessment of value based on the cost utility of a particular procedure compared to alternatives. The existing contribution of geriatric orthopedics to the societal burden of disease is substantial, and literature focusing on the economic value of treating elderly populations with musculoskeletal injuries is growing. Materials and Methods: A literature review of peer-reviewed publications and abstracts related to the cost-effectiveness of treating geriatric patients with orthopedic injuries was carried out. Results: In our review, we demonstrate that while cost-utility studies generally demonstrate net society savings for most orthopedic procedures, geriatric populations often contribute to negative net society savings due to decreased working years and lower salaries while in the workforce. However, the incremental cost-effective ratio for operative intervention has been shown to be below the financial willingness to treat threshold for common procedures including joint replacement surgery of the knee (ICER US8551), hip (ICER US17 115), and shoulder (CE US957) as well as for spinal procedures and repair of torn rotator cuffs (ICER US12 024). We also discuss the current trends directed toward improving institutional value and highlight important complementary next steps to help overcome the growing demands of an older, more active society. Conclusion: The geriatric population places a significant burden on the health care system. However, studies have shown that treating this demographic for orthopedic-related injuries is cost effective and profitable for providers under certain scenarios.